1997
DOI: 10.1159/000154388
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Erythrocyte Pyruvate Kinase Deficiency and Normal Values of Enzyme in a Turkish Population

Abstract: A pyruvate kinase deficiency prevalence study and determination of the normal levels of the enzyme were performed in Antalya city, Turkey. Heparinized blood samples obtained from a representative population of the Antalya province (617 women and 573 men) were tested for pyruvate kinase deficiency by qualitative and quantitative tests between April 1992 and March 1994. The mean pyruvate kinase activity was found to be 19.8 ± 4.0 IU/g Hb whereas the enzyme activity of deficient cases varied between 7.5 and 12.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Some authors have estimated a prevalence of 1∶20 000 in the general white population [23]. In Europe, an incidence of 3.3 per million has been reported in the north of England [24], and a prevalence of 0.24% and 1.1% have been described in Spain [25] and Turkey [26], respectively. In Asia, the frequency of PK deficiency among the Hong Kong Chinese population was <0.1% [27] whilst among the south Iranian population was 1.9% [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have estimated a prevalence of 1∶20 000 in the general white population [23]. In Europe, an incidence of 3.3 per million has been reported in the north of England [24], and a prevalence of 0.24% and 1.1% have been described in Spain [25] and Turkey [26], respectively. In Asia, the frequency of PK deficiency among the Hong Kong Chinese population was <0.1% [27] whilst among the south Iranian population was 1.9% [28].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these sequence variants are missense substitutions affecting residues critical to the structure and/or function of the protein, followed by frameshift and splicing mutations and non-sense; promoter variants and large indels are rare. Recently, compound heterozygous variants with deep intronic mutations have been reported as a cause of PK deficiency (19). Clinical data and in vitro analysis showed that more severe phenotypes are commonly coupled with disruptive sequence variants (stop codon, frameshift, splicing, and large deletions) and with missense variants directly involved in active site or protein stability (8).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, PKLR gene has been under strong selection pressure in malaria-endemic countries, notably, Pakistan and Sub-Saharan Africa [10,11], though hundreds of PKLR mutations are known to cause PK deficiency in humans [9]. Furthermore, the rate of PK deficiency well correlates with the prevalence of consanguinity in countries such as Turkey [19], Iraq [20], Saudi Arabia [21], Iran [22], and the Amish population [23] due to bi-allelic expression of recessive mutations. In Pakistan, an estimated 3.1% neonates with hemolytic anemia have clinically confirmed PK deficiency [24].…”
Section: Discussionmentioning
confidence: 99%